The Effect of Tax Incentives, Tax Rates, Tax Sanctions, Tax Services, and the Application of SAK EMKM on the Compliance of UMKM Taxpayers during the COVID-19 Pandemic: A Case Study of UMKM Taxpayers Registered at KPP Pratama Ternate - Irfan Zamzam; Resmiyati Ansar (Jurnal Ilmiah Akuntansi, 2024)
This study aims to test and analyze the effect of tax incentives, tax rates, tax sanctions, tax services, and the application of SAK EMKM on the compliance of UMKM (Micro, Small, and Medium Enterprises) taxpayers during the COVID-19 pandemic. The research focuses on registered UMKM taxpayers at KPP Pratama Ternate. The method used in this study is quantitative research, with a sample size of 348 respondents. Statistical testing was conducted using SPSS to evaluate the hypotheses. The results indicate that tax incentives, tax rates, and tax services significantly affect the compliance of UMKM taxpayers. However, tax sanctions and the application of SAK EMKM do not have a significant impact on taxpayer compliance. These findings suggest that during the pandemic, supportive measures such as tax incentives and effective tax services are crucial in promoting compliance among UMKM taxpayers. The research provides valuable insights for policymakers and tax authorities to enhance tax compliance through targeted strategies, particularly in challenging economic conditions. By understanding the factors that influence taxpayer behavior, authorities can better support UMKM, ensuring their sustainability and contribution to the economy during and after the pandemic.